2010
DOI: 10.4067/s0717-92002010000100007
|View full text |Cite
|
Sign up to set email alerts
|

Deforestación en ecosistemas templados de la precordillera andina del centro-sur de Chile

Abstract: SUMMARYA multitemporal analysis to determine the land cover change was conduced in the pre-Andean range of Maule region of Chile. We used satellite imagery from the year 1989 and 2003 to analyze the likely causes of native forest change. In this period, there was a reduction in native forest area of 44% in the study area, which is equivalent to an annual forest loss rate of 4.1%. The native forest area is replaced by shrublands (29%) and exotic forest plantations (27%). A great proportion of current exotic for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 40 publications
2
23
0
7
Order By: Relevance
“…In general, temperate forest areas of South America have been rapidly decreasing (Lara et al, 2012). Consequently, increasing forest loss and fragmentation have been the most common trends reported for southern temperate forest landscapes (Echeverría et al, 2006;Altamirano and Lara, 2010;Nahuelhual, 2012, Miranda et al, 2015). However, we suggest that studying local cases and the underlying contexts that may influence native vegetation recovery could potentially be informative for the sustainable management of native forest.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, temperate forest areas of South America have been rapidly decreasing (Lara et al, 2012). Consequently, increasing forest loss and fragmentation have been the most common trends reported for southern temperate forest landscapes (Echeverría et al, 2006;Altamirano and Lara, 2010;Nahuelhual, 2012, Miranda et al, 2015). However, we suggest that studying local cases and the underlying contexts that may influence native vegetation recovery could potentially be informative for the sustainable management of native forest.…”
Section: Discussionmentioning
confidence: 99%
“…Although some forest remnants remain undisturbed, most stands have been replaced or are threatened by anthropogenic activities (Lara et al, 2012;Altamirano and Lara, 2010). In Chile, most landscape change studies have reported the fragmentation and loss of native temperate forest and an increase in exotic tree plantations (Echeverría et al, 2006(Echeverría et al, , 2012Altamirano and Lara, 2010;Nahuelhual, 2012, Miranda et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las perspectivas ecológicas sobre el cambio en el paisaje han tenido un foco en la cuantificación del impacto humano hacia el bosque nativo, con un particular enfoque hacia los patrones de crecimiento y deforestación (Altamirano y Lara, 2010;Armesto et al, 1994). Mediante el análisis de imágenes satelitales, estos estudios han cuantifi cado las transformaciones del uso de suelo, señalando los principales patrones de la desforestación y fragmentación del boque, dando cuenta de cambios sustanciales en la confi guración espacial del bosque nativo (Echeverría et al, 2006;Altamirano y Lara, 2010).…”
Section: Paisajes Forestales Y Colonización En El Sur De Chileunclassified
“…Mediante el análisis de imágenes satelitales, estos estudios han cuantifi cado las transformaciones del uso de suelo, señalando los principales patrones de la desforestación y fragmentación del boque, dando cuenta de cambios sustanciales en la confi guración espacial del bosque nativo (Echeverría et al, 2006;Altamirano y Lara, 2010). Entre los aspectos más relevantes evidenciados por estos estudios se destaca el rápido crecimiento de especies no endémicas asociado con los desarrollos históricos de la industria forestal.…”
Section: Paisajes Forestales Y Colonización En El Sur De Chileunclassified